Typhlodromus (Anthoseius) caudiglans (Schuster) (Acari: Phytoseiidae), The New Record for the Predatory Mite Fauna of Turkey in Erzurum - Kübra Akçakoyunluoğlu; Önder Çalmaşur; Sultan Cobanoglu (Journal of Agricultural Sciences)
Typhlodromus (Anthoseius) caudiglans (Schuster) (Acari: Phytoseiidae) was collected from Hippophae salicifolia L. (Elaeagnaceae) leaves in Erzurum during the years 2015-2016. T. (A.) caudiglans is a predatory mite lives on ornamental plants. The samples were extracted by Berlese funnel and cleared in Lacto-phenol solution after that mounted in Hoyer solution. The samples were deposited in the mite collection at Ankara University and Atatürk University Plant Protection Department of Turkey.This is the first record of T. (A.) caudiglans for Phytoseiidae fauna of Turkey. Re-description and illustration of the new record is given.